دلالة اللفظ العربي.. من معجمية المعنى إلى رحابة السياق القرآني (El-Wahat Journal for Research and Studies, 2017)
The lexical meaning is the first original meaning that inherent the pronunciation of the  meaning and which is  unilateral out of the context. But the existence of the word within the context, brings it  out of its lexical meaning , where it becomes linked to the indications that surround it, as well as to  the different contexts that guide its significance. But when this term is used in The Quran, then we are talking about broader connotations and more distant references. This what distinguishes the Arabic pronunciation in Quranic usage. We have made an applied study of a number of Arabic words used in the Holy Quran with  a clarification of its deep connotations in the context of the  Quran. Keywords – Quranic Context.  the word.  . Lexical Meaning